Strategy to Build a Brand Image of Madrasah Aliyah Al-Amiriyyah Blokagung Banyuwangi - Khasanah, Miratu; Khaudli, Muhammad Imam (Journal of Basic Education Research, 2025)
Purpose of the study: This research aims to analyze the strategies implemented in building brand image and the benefits it brings to madrasas. Methodology: The research method used is qualitative with a case study approach. Data collection was carried out through interviews, observations, and documentation, with research subjects including the head of the madrasah, WKS Humas, education personnel, as well as parents and OSIS. Data analysis techniques include data reduction, data presentation, and drawing conclusions, with data validity checking through source and technique triangulation. Main Findings: This study discusses strategies in building brand image at Madrasah Aliyah (MA) Al-Amiriyyah. Blokagung, Banyuwangi Regency. Educational institutions often face challenges in building their public image. The results of the study showed that the negative image of MA Al-Amiriyyah was caused by an unprofessional publication system. To overcome this, the management of the madrasah implemented various strategies, including excellent programs, to rebuild the image of a quality school. This strategy gradually formed a more positive and attractive school brand for the community.Novelty/Originality of this study: This study presents an update in the study of marketing communication strategies of religious-based educational institutions with a focus on brand image formation at the Madrasah Aliyah level